Identifikasi Somatotype Pada Atlet Beladiri Tarung Derajat Kategori Seni Gerak - Didi Suryadi; Rubiyatno Rubiyatno; Ella Fauziah (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
The magnitude of the benefits that athletes get by knowing their body type, so they can find out what is needed by their sport.However, in practice, not many have done somatotype measurements in selecting prospective athletes. This study aims to determine the effect of the somatotype of the Tarung Derajat martial arts athlete in the Motion Arts category on achievement.This research is descriptive quantitative using survey method.Anthropometric measurement test by measuring bone width, body circumference, body fat thickness, weight and height.Purposive sampling technique is used in determining the sample.The study consisted of 5 male athletes and 10 female Tarung Derajat athletes in the West Kalimantan Movement Art category which was carried out at the Satlat Mujahidin, Pontianak City.The data obtained in the field are the results of the somatotype measurement test and the achievement of Tarung Derajat athletes,then analyzed using descriptive percentage to analyze.The results showed that 67% had an endomorph mesomorph body type as many as 2 athletes with local achievements and 8 athletes with national achievements, central body type as many as 2 athletes have local achievements with a percentage of 13%, endomorph body types have 1 local achievement and 1 national athlete with a percentage of 13%, the next mesomorph ectomorph body type 7% with local achievements. The conclusion is that the endomorph mesomorph somatotype has a positive influence on the performance of combat athletes in the movement arts category, thus the results of this study provide a new reference regarding somatotypes in martial athletes.